Surgical correction of vesico‐ureteric reflux for recurrent febrile urinary tract infections after kidney transplantation. (27th February 2013) - Dinckan, Ayhan; Aliosmanoglu, Ibrahim; Kocak, Huseyin; Gunseren, Filiz; Mesci, Ayhan; Ertug, Zeki; Yucel, Selcuk; Suleymanlar, Gultekin; Gurkan, Alihan
Abstract : Objective: To evaluate the outcome of anti‐reflux revision surgery in patients diagnosed with at least a grade 3 reflux at voiding cysto‐urethrography in patients with recurrent urinary tract infection (UTI) after renal transplantation. Patients and Methods: We identified 60 patients with a diagnosis of recurrent febrile UTI and post‐transplantation vesico‐ureteric reflux (VUR) who underwent open surgical correction of reflux. Patient characteristics, including the aetiology of end‐stage renal disease, age, time to VUR correction, type of VUR correction, serum creatinine levels, and number of UTIs before and after correction were documented. Results: The median (range) age of the patients was 31.5 (9–65) years. A total of 30 patients underwent uretero‐ureterostomy or pyelo‐ureterostomy and 30 underwent extravesical or intravesical ureteric reimplantation. The median (range) creatinine levels before and after correction were 1.5 (0.8–4.5) mg/dL and 1.3 (0.7–4.5) mg/dL ( P  < 0.05), respectively. The median (range) number of UTI episodes reported before the correction surgery was 4 (3–12), whereas number of UTI episodes after the surgery was 1 (0–12), the difference being significant ( P  < 0.05). Conclusions: Open surgical correction of post‐transplant VUR is an effective and safe method of decreasing UTI episodes and stopping reflux. Surgical correction of reflux may prolong the life of the renal graft.